Laparoscopic versus open repair of perforated peptic ulcer: Improving outcomes utilizing a standardized technique - Siow, Sze Li; Mahendran, Hans Alexander; Wong, Cheeming; Hardin, Mark O.; Luk, Tienloong (Elsevier (Singapore) Pte Ltd, 2016)
Background/Objective: The objective of this study was to compare the outcomes of patients who underwent laparoscopic and open repair of perforated peptic ulcers (PPUs) at our institution. Methods: This is a retrospective review of a prospectively collected database of patients who underwent emergency laparoscopic or open repair for PPU between December 2010 and February 2014. Results: A total of 131 patients underwent emergency repair for PPU (laparoscopic repair, . n=63, 48.1% vs. open repair, . n=68, 51.9%). There were no significant differences in baseline characteristics between both groups in terms of age (p=0.434), gender (p=0.305), body mass index (p=0.180), and presence of comorbidities (p=0.214). Both groups were also comparable in their American Society of Anesthesiologists (ASA) scores (p=0.769), Boey scores 0/1 (p=0.311), Mannheim Peritonitis Index > 27 (p=0.528), shock on admission (p . <. 0.99), and the duration of symptoms > 24 hours (p=0.857). There was no significant difference in the operating time between the two groups (p=0.618). Overall, the laparoscopic group had fewer complications compared with the open group (14.3% vs. 36.8%, . p=0.005). When reviewing specific complications, only the incidence of surgical site infection was statistically significant (laparoscopic 0.0% vs. open 13.2%, . p=0.003). The other parameters were not statistically significant. The laparoscopic group did have a significantly shorter mean postoperative stay (p=0.008) and lower pain scores in the immediate postoperative period (p . <. 0.05). Mortality was similar in both groups (open, 1.6% vs. laparoscopic, 2.9%, . p < 0.99). Conclusion: Laparoscopic repair resulted in reduced wound infection rates, shorter hospitalization, and reduced postoperative pain. Our single institution series and standardized technique demonstrated lower morbidity rates in the laparoscopic group